45, 610–52, 160 years of site and landscape occupation at Nawarla Gabarnmang, Arnhem Land plateau (northern Australia). (1st July 2019) - David, Bruno; Delannoy, Jean-Jacques; Mialanes, Jerome; Clarkson, Christopher; Petchey, Fiona; Geneste, Jean-Michel; Manne, Tiina; Bird, Michael I.; Barker, Bryce; Richards, Thomas; Chalmin, Emilie; Castets, Géraldine
Abstract: We present Bayesian modelling on a long sequence of radiocarbon ages from the archaeological site of Nawarla Gabarnmang, central Arnhem Land plateau, northern Australia. A horizon of wind-borne sediments containing flaked stone artefacts and charcoal commencing >45, 610 cal BP (the young end of the modelled boundary age range, which extends beyond the limit of the calibration curve), with a median modelled age of 48, 500 cal BP, signals the onset of aeolian mobilisation of fine sands and silts across the landscape, and re-deposition within the site at a time synchronous with the first evidence of people. This earliest cultural horizon (Stratigraphic Unit 4) contains 509 stone artefacts, and is marked by a contemporaneous sedimentary break, from underlying culturally sterile sediments consisting of disintegrating roof-fall and in situ sandstone and quartzite to overlying culturally-rich wind-blown sand. The new radiocarbon ages and wind-blown sediments together provide evidence for the commencement of noticeable landscape burning on the Arnhem Land plateau c. 48, 500 cal BP, suggesting an intensification of landscape management practices at the summit of the Arnhem Land plateau some 10, 000–15, 000 years after the lowest dense band of artefacts (Phase 2) at Madjedbebe on the floodplains 90 km to the north. These results have ramifications for the structure and timing of the spread of people across Australia, and the extinction of megafauna in Sahul. Highlights: Radiocarbon ages spanning the past c. 48, 500 years of human occupation are presented for Nawarla Gabarnmang, north Australia. Earliest flaked stone artefacts and in situ charcoal appear in tandem. The first stone artefacts and charcoal appear within the site with the onset of aeolian sediments. The earliest artefacts, in situ charcoal and aeolian sediments overlie soft sediments originating from roof-fall. The onset of aeolian sediments with artefacts and charcoal in the site suggest anthropic landscape modifications 45, 610–52, 160 years ago. These results suggest permanent occupation of the rugged Arnhem Land plateau > 10, 000 years after the northern floodplains.